Effect of hypoxia-inducible factor-prolyl hydroxylase inhibitors on anemia in patients with CKD: a meta-analysis of randomized controlled trials including 2804 patients. Issue 1 (1st January 2020) - Wang, Bin; Yin, Qing; Han, Yu-Chen; Wu, Min; Li, Zuo-Lin; Tu, Yan; Zhou, Le-ting; Wei, Qing; Liu, Hong; Tang, Ri-Ning; Cao, Jing-Yuan; Lv, Lin-Li; et al.
Abstract: Hypoxia-inducible factor-prolyl hydroxylase inhibitors (HIF-PHIs) are orally active first-in-class new generation drugs for renal anemia. This extensive meta-analysis of randomized controlled trials (RCTs) was designed to provide clear information on the efficacy and safety of HIF-PHIs on anemia in chronic kidney disease (CKD) patients. Searches included PubMed, Web of Science, Ovid MEDLINE, and Cochrane Library database up to October 2019. RCTs of patients with CKD comparing HIF-PHIs with erythropoiesis-stimulating agents (ESAs) or placebo in the treatment of anemia. The primary outcome was hemoglobin change from baseline (Hb CFB); the secondary outcomes included iron-related parameters and the occurrence of each adverse event. 26 trials in 17 articles were included, with a total of 2804 dialysis or patients with CKD. HIF-PHIs treatment produced a significant beneficial effect on Hb CFB compared with the placebo group (MD, 0.69; 95% CI, 0.36 to 1.02). However, this favored effect of HIF-PHIs treatment was not observed in subgroup analysis among trials compared with ESAs (MD, 0.06; 95% CI, −0.20 to 0.31). The significant reduction in hepcidin by HIF-PHIs was observed in all subgroups when compared with the placebo group, whereas this effect was observed only in NDD-CKD patients when compared with ESAs. HIF-PHIs increased the risk of nausea (RR, 2.20; 95% CI, 1.06 to 4.53) and diarrhea (RR, 1.75; 95% CI, 1.06 to 2.92). We conclude that orally given HIF-PHIs are at least as efficacious as ESAs treatment to correct anemia short term in patients with CKD. In addition, HIF-PHIs improved iron metabolism and utilization in patients with CKD.